2003
DOI: 10.1111/1540-6261.00577
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Compensation When Executives Can Hedge the Market: Evidence of Relative Performance Evaluation in the Cross Section

Abstract: Little evidence exists that ¢rms index executive compensation to remove the in£uence of marketwide factors. We argue that executives can, in principle, replicate such indexation in their private portfolios. In support, we ¢nd that market risk has little e¡ect on the use of stock-based pay for the average executive. But executives'ability to ''undo''excessive market risk can be hindered by wealth constraints and inalienability of human capital.We replicate the standard result that there is little relative perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
184
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(197 citation statements)
references
References 33 publications
(55 reference statements)
10
184
3
Order By: Relevance
“…Moreover, as mentioned above, the firm may want to offer a contract which preempts managerial hedging (by performing hedging on her account), and this also leads to the dependence of the payoff on the risk factors driving the hedging opportunities. This is in agreement with findings of Jin (2002) and Garvey and Milbourn (2003), who find that RPE should be used when the managers are constrained in their hedging opportunities, while there is no need for RPE if the managers have low cost of hedging. In relation to this, it should be mentioned that in our first-best world there may be more than one optimal contract, and we only consider the contracts which induce the manager not to hedge, which we call hedge-neutral contracts, which may then include the RPE component even when managerial hedging is costless.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, as mentioned above, the firm may want to offer a contract which preempts managerial hedging (by performing hedging on her account), and this also leads to the dependence of the payoff on the risk factors driving the hedging opportunities. This is in agreement with findings of Jin (2002) and Garvey and Milbourn (2003), who find that RPE should be used when the managers are constrained in their hedging opportunities, while there is no need for RPE if the managers have low cost of hedging. In relation to this, it should be mentioned that in our first-best world there may be more than one optimal contract, and we only consider the contracts which induce the manager not to hedge, which we call hedge-neutral contracts, which may then include the RPE component even when managerial hedging is costless.…”
Section: Introductionsupporting
confidence: 92%
“…It would be of interest, but not easy, to extend that framework to the moral hazard case of unobserved risk taking actions, with non-CARA preferences and nonlinear contracts. 9 Moreover, as option compensation may be partly motivated by a need to distinguish between managers of varying abilities, one would like to see the incentive effects studied when the type of the manager is unknown, namely, the case of adverse selection. Similarly, the firm might not know what assets the manager has available for hedging, and in particular, it might not know the correlation between those assets and the firm's output.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most prior research focuses on the observed characteristics in order to address particular theories. 5 When regressing the level of executive pay on explanatory variables, some papers control for firm fixed effects (Bertrand and Mullainathan, 2001, Chhaochharia and Grinstein, 2009, Frydman and Saks, 2010, Gabaix and Landier, 2008, Hubbard and Palia, 1995, Joskow et al, 1996, Kraft and Niederprum, 1999, Perry and Zenner, 2001), a few papers control for manager fixed effects (Aggarwal and Samwick, 1999, Garvey and Milbourn, 2003, Perry and Zenner, 2001, and none control for both at the same time. All these prior studies focus on observable determinants.…”
Section: Introductionmentioning
confidence: 99%